The impacts of wind power on power systems operation - Ferreira, Paula Varandas (2007)
The wind power sector is growing rapidly in Portugal and the National objectives for energy include a significant increase of wind power during the next years. The large penetration of wind power in Portugal will influence significantly the energy system cost, but it seems also essential to materialize the international energetic and environmental commitments. This paper focuses on the impact of large scale wind scenarios on the power system operation. CO2 abatement potential is estimated along with the effects on the operating costs of thermal power plants. Simulations for different wind scenarios were run for 2016, assuming the possibility of exports. According to the results, it seems that about 20% of wind power penetration may be achieved in Portugal with minor losses of efficiency of the global system.